2016
DOI: 10.1128/iai.00007-16
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrated Macrophages Die of Pneumolysin-Mediated Necroptosis following Pneumococcal Myocardial Invasion

Abstract: dStreptococcus pneumoniae (the pneumococcus) is capable of invading the heart. Herein we observed that pneumococcal invasion of the myocardium occurred soon after development of bacteremia and was continuous thereafter. Using immunofluorescence microscopy (IFM), we observed that S. pneumoniae replication within the heart preceded visual signs of tissue damage in cardiac tissue sections stained with hematoxylin and eosin. Different S. pneumoniae strains caused distinct cardiac pathologies: strain TIGR4, a serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 44 publications
5
73
0
Order By: Relevance
“…After crossing the vascular endothelium, S. pneumoniae damages the myocardium, creating bacterium-associated microlesions. Our published studies using immunofluorescence microscopy suggest that this begins with the interaction of a single pneumococcus with surrounding cardiomyocytes (15). A trypan blue exclusion assay showed that at a low multiplicity of infection (MOI), i.e., less than 10 bacteria per cardiomyocyte, S. pneumoniae was able to induce cell death in approximately 60% of HL-1 cardiomyocytes after 6 h of infection in vitro, without detachment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After crossing the vascular endothelium, S. pneumoniae damages the myocardium, creating bacterium-associated microlesions. Our published studies using immunofluorescence microscopy suggest that this begins with the interaction of a single pneumococcus with surrounding cardiomyocytes (15). A trypan blue exclusion assay showed that at a low multiplicity of infection (MOI), i.e., less than 10 bacteria per cardiomyocyte, S. pneumoniae was able to induce cell death in approximately 60% of HL-1 cardiomyocytes after 6 h of infection in vitro, without detachment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2). Pneumolysin is a pore-forming toxin produced by S. pneumoniae (24), and its role in cardiomyocyte killing has already been demonstrated, albeit at late stages of microlesion formation or when administered extracellularly (13,15). In contrast, SpxB is a metabolic enzyme that generates H 2 O 2 as a result of converting pyruvate to acetylphosphate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several bacterial pathogens with pore-forming toxins induce macrophage necroptosis, a pro-inflammatory mode of cell death regulated by receptor interacting protein kinases RIP1 and RIP3 and mediated by the effector mixed-lineage kinase domain-like protein MLKL; macrophages deficient in MLKL are consequently resistant to pore-forming toxin-induced cell death. Treatment of mice with necrostatin-5, an inhibitor of RIP1 and/or GW806742X, an inhibitor of MLKL, reduced severity of Serratia marcescens pneumonia in mice, protecting alveolar macrophages from cell death and reducing bacterial burden [33]; necrostatin-5 also reduced pneumolysin-mediated macrophage necroptosis and cardiac damage following pneumococcal bacteremia and myocardial invasion [34]. …”
Section: Neutralization Of Virulence Factors: Disarming the Pathogenmentioning
confidence: 99%